The liability of companies for work accidents in the São Paulo labor judiciary-TRT15 - Arruda, Rodrigo Chavari de [UNESP]; Cavalcante, Sandra Regina; Almeida, Ildeberto Muniz de [UNESP] (Univ Sao Paulo, Fac Saude Publica, 2023)
The risk theory or objective liability dispenses proof of guilt or intent and requires only the occurrence of damage and the causal link. Although the constitution establishes the responsibility for work accidents as subjective, it has been observed in the doctrine and in the judiciary the adoption of objective liability in some cases of accidents and occupational diseases. This study aims to analyze the decisions of the Regional Labor Court of the 15th Region - Sao Paulo to know in which situations the court has used objective liability. The quantitative-qualitative, exploratory and descriptive research was developed based on document analysis and literature review. The document research was carried out in judgments that contained the descriptor work accident, available in the database of the Regional Labor Court of the 15th Region, judged between 11/11/2015 and 10/11/2017. The results indicated that, of the total of 559 cases judged, in 275 the decision was founded, being 15% by objective liability. Considering only the founded cases, objective liability appeared in 30.5% of them. This percentage reveals that decision-making based on the notion of objective liability is already expressive in this court, and that such adoption has the potential to affect accident prevention practices.
Keywords: Civil Liability; Workers' Compensation; Case law; Occupational Health